2021
DOI: 10.1177/10547738211060602
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiovascular Diseases Knowledge and Risk Factors Among Adult Population in the South Region of Saudi Arabia

Abstract: Cardiovascular diseases are the main cause of mortality and disability worldwide. This study aimed to assess knowledge of cardiovascular disease and risk factors among the adult population in the south region of Saudi Arabia. A web-based cross-sectional survey of 1,049 participants was completed during August 2021. Data were collected by using 25-item heart disease fact questionnaire. The study population included 526 men (50.1%) and 523 women (49.9%) with a mean age of 36 ± 12 years. The average total knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…Our findings revealed that 70.3% of participants reported a high level of knowledge regarding coronary artery disease risk factors, while 27.4% had a medium level, and only 2.3% exhibited a low level of knowledge. Similar results were reported in the southern region of Saudi Arabia, where 51.3% had good knowledge, 27.4% had moderate knowledge, and 21.3% had poor knowledge [ 10 ]. However, in Riyadh Province of Saudi Arabia, a study reported poor knowledge among respondents regarding both coronary artery disease risk factors and preventive measures [ 11 ].…”
Section: Discussionsupporting
confidence: 82%
“…Our findings revealed that 70.3% of participants reported a high level of knowledge regarding coronary artery disease risk factors, while 27.4% had a medium level, and only 2.3% exhibited a low level of knowledge. Similar results were reported in the southern region of Saudi Arabia, where 51.3% had good knowledge, 27.4% had moderate knowledge, and 21.3% had poor knowledge [ 10 ]. However, in Riyadh Province of Saudi Arabia, a study reported poor knowledge among respondents regarding both coronary artery disease risk factors and preventive measures [ 11 ].…”
Section: Discussionsupporting
confidence: 82%
“…The total mean knowledge score of the Arabic-speaking sample was 11.3 (SD = 3.8), the lowest among all previous studies using the CADE-Q SV. Indeed, previous studies have identified a lack of awareness and knowledge of people living with CVD and its risk factors in the GCC region [ 6 , [36] , [37] , [38] , [39] ]. CADE-Q SV can support clinicians in identifying knowledge gaps – so they can be addressed during consultations – along with guiding healthcare providers to what areas patients need to learn most.…”
Section: Discussionmentioning
confidence: 99%
“… 15 On the contrary, another study from the southern region of Saudi Arabia reported a high prevalence of CVD risk factors, in addition, previous findings also reported inadequate knowledge among the Saudi population about CVDs. 16 …”
Section: Introductionmentioning
confidence: 99%
“… 4 , 17 , 18 For instance, the knowledge of CVDs among healthcare professionals were good, 17 while among CVD patients it was suboptimal, 17 among diabetes patients it was satisfactory, 4 , 19 while the knowledge among public perspective was low both nationally and internationally. 16 , 20 Therefore, it is essentially important to assess the CVD knowledge among the public to create more awareness about the disease, thereby preventing the possible adverse outcomes associated with the Risk of CVD. Furthermore, studies on knowledge of CVD risk factors and its primary prevention practices among the Saudi public are rare in Saudi Arabia and other international countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation